Analisis Pengukuran Ergonomi Metode ROSA Saat Perkuliahan Daring: Studi Kasus Mahasiswa Teknik Industri UBSI - Destiana Putri; Miwan Kurniawan Hidayat (LPPM Universitas Bina Sarana Informatika, 2022)
Last year's learning activities at home or studying from home were carried out by a number of schools and the office sector due to the new type of corona virus (SARS-CoV-2) that causes Covid-19. This change in activity can have a negative impact on both physical and mental complaints that may occur due to behavior during lecture activities. During lectures there are still many of us who have not paid attention to the correct and safe position when conducting online meetings such as sitting position, distance between the computer screen and head, foot position, working or study room conditions, correct hand position and so on. So it is important for us to understand the definition of ergonomics in order to reduce the work risks that occur and determine a safer body position to do. Efficiency of human–computer interaction as well as user comfort, health and safety can be improved by applying ergonomic principles. Based on this, the purpose of this study is to identify student behavior during lectures, measure physical complaints (MSD and visual fatigue) and provide recommendations to minimize negative impacts that occur using the ROSA (Rapid Office Strain Assessment) method. With this method, it can be seen that some students surveyed using the ROSA method resulted in a final score of 2 which means they have a low level of danger, but must still pay attention to various aspects of sitting in a sitting position while doing lectures by avoiding the use of smartphones in a non-sitting position. chair so as not to pose a risk of dangerous disease.